97.8k views
3 votes
Can someone help me with this ??

Can someone help me with this ??-example-1
User Om Kumar
by
6.0k points

1 Answer

6 votes

Answer:


\frac{\bf{cd^7}}{\bf{c^6d \cdot c^4d^9}}=\frac{\bf{1}}{\bf{c^9d^3}}

Explanation:

Given expression is
(cd^7)/(c^6d \cdot c^4d^9)


(cd^7)/(c^6 d \cdot c^4d^9)=(c d^7)/(c^(10)d^(10)) by using the formula
a^m+a^n=a^((m+n))


(c d^7)/(c^6 d\cdot c^4d^9)=(c)/(c^(10))\cdot(d^7)/(d^(10))


(c d^7)/(c^6 d\cdot c^4d^9)=(c^-9)/(d^-3) by using the formula
(a^m)/(a^n)=a^((m-n))


(c d^7)/(c^6 d\cdot c^4d^9)=(1)/(c^9d^3) by using the formula
(1)/(a^m)=a^(-m)

User Brent Rockwood
by
6.8k points